PEMBANGUNAN APLIKASI PERSEDIAAN BERAS BULOG PADA KANTOR LURAH PARAK LAWEH PULAU AIE NAN XX KOTA PADANG - Anisya (Jurnal Teknoif Teknik Informatika Institut Teknologi Padang, 2013)
In Parak Laweh Pulau Aie Nan XX has activity what is distribution government rice for peoples who depend of in this activity . Purpose of this researches are help out especially Aisyiyah’s Hospital in care-inpatient e-data processing with building a information system using PHP programming language and MySQL Databases.